Floods and Railways in Nineteenth-Century New Zealand - Brett, Andre (University of Auckland, 2019)
Focuses on the relationship between railways and flooding in New Zealand between 1863 and 1900. Explores how railways affected water flow and vice versa. Elucidates three key themes drawn from railway records: the evolution of the response of officials and engineers to different environments; the changing effects of floods in environments that were re-made by railways; and the costs of floods. Looks at railways built prior to 1878, and how engineers took waterflows into account when designing railways and preventative works. Details the effects and consequences of the great flood that started on the east coast of the South Island on 28 Jun 1879 and greatly affected the entire South Island railway system. Describes other flooding events in Manawatū-Whanganui from 1880 to 1882. Discusses flooding of mountain railways, particularly a huge flood in Grey Country in Feb 1899.